Role of Muscle Free Flap in the Salvage of Complicated Scalp Wounds and Infected Prosthetic Dura - Han, Dae Hee; Park, Myong Chul; Park, Dong Ha; Song, Hyunsuk; Lee, Il Jae (Archives of Plastic Surgery, 2013)
Background The prosthetic dura is an essential element in the protection of the cranial parenchyma and prevention of cerebrospinal fluid leakage. Although prosthetic dura are widely used in neurosurgery, they occasionally provoke infection, which can be a major concern after neurosurgical treatment. However, removal of the prosthetic dura carries a risk of brain parenchyma injury and cerebrospinal fluid leakage. The salvage of infected prosthetic dural material has not been adequately addressed in the literature. In this study, we demonstrate the value of the combination of a meticulous surgical debridement of necrotic tissue and simultaneous muscle free flap for intractable postoperative epidural abscess without removal of the infected prosthetic dura.Methods Between 2010 and 2012, we reviewed the data of 11 patients with persistent infection on the prosthetic dura. The epidural infections each occurred after a neurosurgical procedure, and there was soft tissue necrosis with the disclosure of the underlying prosthetic dura and dead bone around the scalp wound. To salvage the infected prosthetic dura, meticulous debridement and a muscle free flap were performed.Results All 11 patients experienced complete recovery from the complicated wound problem without the need for further surgical intervention. No signs of prosthetic dural infection were observed during the mean follow-up period of 11 months.Conclusions The combination of a meticulous surgical debridement and coverage with a muscle free flap is an effective treatment for salvage of infected prosthetic dura.
Keywords: Free tissue flaps; Epidural abscess; Salvage therapy; Prosthesis-related infections